Exploring the socio-emotional factors associated with subjective well-being in the unemployed - Berrios,M. Pilar; Extremera,Natalio; Nieto-Flores,M. Pilar (PeerJ, 2016)
In this study, we examined the relations between dimensions of Perceived Emotional Intelligence (PEI) and classic constructs, such as social support, on depression, stress, and subjective well-being indicators (life satisfaction and happiness). The study also sought to determine whether PEI dimensions accounted for a significant portion of the variance beyond that of classic constructs in the study of depression, stress, and well-being outcomes in a sample of 442 unemployed subjects. Results indicated that social support and all PEI dimensions are found to be significant and negatively related to depression and stress, and these variables were also found to be significant and positively associated with life satisfaction and happiness. Additionally, results using regression analysis indicated that PEI, and specifically use of emotions and regulation of emotions, explain a significant amount of the variance of all outcomes after controlling for socio-demographics and social support dimensions. Finally, theoretical and practical implications of these constructs and their relation with psychological adjustment and well-being in unemployed people are discussed.
Keywords: Unemployed; Well-being; Social support; Depression; Emotional intelligence; Stress